Social justice education, globalization, and teacher education - Nganga, Lydiah; Kambutu, John (Emerald Publishing Limited : Information Age Publishing, Inc., 2016)
The primary purpose of this book is to serve as a resource in teacher preparation programs. It is also intended to serve as an instructional resource in P-12 education. The book will be especially useful in methods of teaching and foundational courses both at the elementary and secondary education levels. The book contains pertinent instructional topics, units and lessons in global education and social justice themes. The secondary purpose of this book is to serve as a resource for graduate students and researchers whose interest is global and social justice education.This unique book provides for an interdisciplinary approach to teacher education. Additionally, this book is intended to create a deeper sense of relevancy to issues of curriculum in teacher education. Together, global educators and social justice educators can forge pedagogical content knowledge that bridges the gap between affirming one's own identity and maintaining unity with the whole, thus exemplifying a robust notion of social justice. Consequently, content in this book will help pre-service teachers to gain confidence and deeper knowledge around issues of global interest, responsibilities and uncertainties associated with their role as teachers who will teach children within the intersection of local and international neighborhoods.
Keywords: Social justice -- Study and teaching.; Teachers -- Training of -- Social aspects.; Education and globalization.; Education -- Philosophy, Theory & Social Aspects.; Educational strategies and policy: inclusion.; Philosophy and theory of education.; elektronické knihy; electronic books